2023
DOI: 10.3390/aerospace10020164
|View full text |Cite
|
Sign up to set email alerts
|

A Fault Diagnosis Method under Data Imbalance Based on Generative Adversarial Network and Long Short-Term Memory Algorithms for Aircraft Hydraulic System

Abstract: Safe and stable operation of the aircraft hydraulic system is of great significance to the flight safety of an aircraft. Any fault may be a threat to flight safety and may lead to enormous economic losses and even human casualties. Hence, the normal status of the aircraft hydraulic system is large, but very few data samples relate to the fault status. This causes a data imbalance in the fault diagnosis of the aircraft hydraulic system, which directly affects the accuracy of aircraft fault diagnosis. To solve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Notably, this approach exhibited excellent performance in diagnosing faults in three-phase PMSM drive system inverters, leading to improved classification and recognition accuracy. Comparative tests conducted in references [34,35], involving various algorithms, revealed that the proposed SDAE-GAN-LSTM method consistently produced experimental results either comparable to or superior to existing methods. This substantiates the superiority and effectiveness of the SDAE-GAN-LSTM approach in fault diagnosis.…”
Section: Comparison With Typical Fault Diagnosismentioning
confidence: 91%
See 2 more Smart Citations
“…Notably, this approach exhibited excellent performance in diagnosing faults in three-phase PMSM drive system inverters, leading to improved classification and recognition accuracy. Comparative tests conducted in references [34,35], involving various algorithms, revealed that the proposed SDAE-GAN-LSTM method consistently produced experimental results either comparable to or superior to existing methods. This substantiates the superiority and effectiveness of the SDAE-GAN-LSTM approach in fault diagnosis.…”
Section: Comparison With Typical Fault Diagnosismentioning
confidence: 91%
“…This approach significantly improved fault diagnosis accuracy, serving as a foundation for evaluating the effectiveness of the SDAE-GAN-LSTM method across diverse applications. In the context of time series data, reference [35] introduced an enhanced model structure tailored toward tackling sample imbalance problems. This method, employing LSTM as the classifier, achieved progressively higher accuracy as the number of fault samples increased.…”
Section: Comparison With Typical Fault Diagnosismentioning
confidence: 99%
See 1 more Smart Citation